The importance of measuring dispersion in firm-level outcomes - Chad Syverson (IZA World of Labor, 2014)
Recent research has revealed enormous variation in performance and growth among firms, which both drives and is driven by large reallocations of inputs and outputs across firms (churning) within industries and markets. These differences in firm-level outcomes and the associated turnover of firms affect many economic policies (both labor- and non-labor-oriented), on both a microeconomic and a macroeconomic scale, and are affected by them. Properly evaluating these policies requires familiarity with the sources and consequences of firm-level variation and within-industry reallocation.
Keywords: D2; E23; J2; L11; L2; O4; 330; microdata; productivity; growth; employment; churning; misallocation